The association between the isokinetic muscle strength and lower extremity injuries in young male football players - Namazi, P.; Zarei, M.; Hovanloo, F.; Abbasi, H. (Physical Therapy in Sport, 2019)
Background: Validating any screening test to predict and prevent football injuries is in need of identifying related risk factors through prospective designs. In spite of the extensive use of strength testing in football players, there are limited studies investigating the relationship between isokinetic muscle strength and injury risk in young football players. The present study aimed to evaluate the relationship between isokinetic strength and the risk of lower extremity injury among Iranian young football players. Method: ology: seventy three U-21 football players participated in this study. Isokinetic strength of hip,knee and ankle muscles were measured using the Isokinetic system pro 4. Injuries and exposure in training and matches were registered prospectively by club medical staff for one season. Results: Significant relationships were revealed between the isokinetic strength of hip abductor and adductor muscles, and isokinetic strength ratio of hip abductor/adductor muscles at an angular speed of 30 /sec, the isokinetic strength of hip abductor muscles at 90 /sec, and isokinetic strength of knee flexor and extensor muscles at 60 /sec and knee flexor/extensor strength ratio at angular velocities of 60 /sec with the injury occurrence among football players. Conclusion: lower extremity isokinetic strength indices are associated with injuries in young male football players.